Aplikasi Inokulasi Plant Growth Promoting Rhizobacteria dengan Sistem Tumpangsari Menuju Peningkatan Efisiensi Air dan Hara yang terbatas di Lahan Kering di Nusa Tenggara Barat - Putri Yunita Wahyuti; Suwardji Suwardji; Lolita Endang Susilowati; Mulyati Mulyati (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This research was conducted to systematically examine scientific evidence regarding the mechanisms and synergistic impacts of PGPR and intercropping on Water Use Efficiency (WUE) and Nutrient Use Efficiency (NUE) in drylands. The method used was a systematic literature study with a search for peer-reviewed articles and strict selection of research evaluating WUE and NUE parameters in intercropped crops and crops inoculated with PGPR. The results showed that intercropping systems can increase soil water retention, improve microclimate conditions, and optimize the utilization of space and nutrients between plant species. PGPR contributes to improving plant growth through nitrogen fixation mechanisms, phosphate dissolution, phytohormone production, and strengthening tolerance to drought stress. The synergy between these two approaches enhances the plant's ability to utilize water and nutrients more efficiently, thereby implying an increase in productivity and sustainability of dryland agricultural systems. These findings emphasize the need for verification through field trials, development of adaptive local PGPR isolates, and institutional and policy support to expand the application of this technology to drylands.